Enough : your health, your weight, and what it's like to be free - Jastreboff, Ania M.; Winfrey, Oprah (Avid Reader Press, 2026)
"For her entire adult life, Oprah Winfrey has struggled with her weight. She never thought in her lifetime, medicines would provide hope, health, and healing for people like her. But as her conversations with Dr. Ania Jastreboff from the Yale School of Medicine reveal, we've learned that having obesity is not a choice. It's not a question of willpower. Obesity is a disease. It's a question of biology, created by our bodies' need to survive and the environment we created and now live in. And it's treatable. The new medications can lower our body fat set point (our brain's "Enough Point"), so that we lose weight without battling biology with willpower. Dr. Jastreboff describes strategies to optimize health and manage side effects all with the reassuring perspective of decades of experience treating patients with obesity and leading studies with these medications. Many of her patients say the "food noise" that plagued them for years has evaporated. They describe a new freedom from intrusive, persistent, and disruptive thoughts about food. With treatment they begin a journey of healing with self-compassion, devoid of the shame and blame they've endured from society for decades. Oprah says she's learned so much from Dr. Jastreboff about how, when it comes to weight, our bodies work with us--and also against us. How each of our struggles are different and each of our choices in living with obesity may also be different. Dr. Jastreboff's groundbreaking research offers a new way forward, not only for obesity treatment, but also for overall health, with significant implications for the prevention and reversal of hundreds of related diseases. As she demonstrates in this book, when science meets empathy, real healing becomes possible. Yes, there is a path to healing and leading the life you have always wanted, when your brain is reassured that you have "enough." -- Provided by the publisher.